Peningkatan Kreativitas Berkarya Seni Rupa Materi Penerapan Ragam Hias pada Bahan Tekstil Melalui Praktik Membatik dengan Teknik Lukis Siswa Kelas VII A SMP Negeri 2 Panggul - Jatmika, Surya Hadi Widi (Jurnal Simki Pedagogia, 2022)
In the material of Applying Ornaments to Artificial Materials, many students of class VII A are found who are unable to develop their creativity in applying decoration to textile media through batik work because students do not feel interested in the material so that the results are not satisfactory. This is evidenced by the 28 students of class VII A consisting of 13 male students and 15 female students, 9 students or 32% of students who completed their studies, while 19 students who did not complete their studies or 67.8% with an average grade 66. The value obtained by the student has not reached the KKM for Cultural Arts which is set at 70. The purpose of this study is to obtain an objective answer about increasing creativity in the work of Fine Arts in the material Applying Ornaments to Artificial Materials with the indicator that students are able to apply decoration to the media. textiles through batik work using painting techniques in Semester 1 of the 2019/2020 academic year at SMP Negeri 2 Panggul. This research method is classroom action research using the cycle model of Kemmis and Mc. Taggart with four stages in each cycle, namely planning, implementation, action, observation and reflection. Data collection techniques through monitoring results, actions, analysis of learning activities, field notes, and data collection using documentation taken during the learning process. The results of batik creativity with painting techniques obtained in the first cycle is 32% and the second cycle is 85.65%. The average percentage of the monitoring data for the first cycle is 85% and the second cycle is 95%. From the analysis of the data above, it can be concluded that learning by using batik painting techniques can increase students' creativity.